6=-3(x-5)

Simple and best practice solution for 6=-3(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=-3(x-5) equation:


Simplifying
6 = -3(x + -5)

Reorder the terms:
6 = -3(-5 + x)
6 = (-5 * -3 + x * -3)
6 = (15 + -3x)

Solving
6 = 15 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6 + 3x = 15 + -3x + 3x

Combine like terms: -3x + 3x = 0
6 + 3x = 15 + 0
6 + 3x = 15

Add '-6' to each side of the equation.
6 + -6 + 3x = 15 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 15 + -6
3x = 15 + -6

Combine like terms: 15 + -6 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

See similar equations:

| 63=5x^2-26x | | x-(-38)=43 | | 8n+18=360 | | 7y=39 | | 7w-15-5w=43 | | 4+x-9+x=7 | | -1=11-x+3 | | 48+d+2(30-4d)=d | | 3+5q=15-7q | | 8x^2-56x+80=0 | | x+7y=39 | | -23-4p=19-p | | 8-y-4y=-22 | | 2m-15=9m+20 | | X^2-14X+50=0 | | 9a-6=7a+1 | | -9+8w=3w-24 | | 2(x-3)=-16 | | -y+2-y+2=8 | | 4v+13=-v+13 | | 3x^2-12x-39=0 | | 10=6-4x-8 | | -6u+11=7u-28 | | 12-7n=2n+30 | | 3c+25=-35-c | | b+8=-4b+53 | | 4a-6=-38 | | 7y+8x=10 | | 2(2k-1)+4(3k+1)=18 | | 5r-46=13r+10 | | 24-7k=k | | 5x+4x=180 |

Equations solver categories